2010
DOI: 10.1007/s11883-009-0072-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia in Youth: Opportunities and Obstacles to Prevent Premature Atherosclerotic Cardiovascular Disease

Abstract: Treatment of hypercholesterolemia in youth is predicated on the knowledge that we can identify those youth with this atherosclerotic risk factor most likely to develop premature cardiovascular disease. Unfortunately, this is not the case. Before we can adequately address appropriate lipid-lowering therapies in this special population, we must address and resolve current barriers related to screening and diagnosis. In this article, we describe some of the opportunities and obstacles that clinicians and policy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 47 publications
0
20
0
1
Order By: Relevance
“…The prevention of cardiovascular diseases must begin decades prior to the onset of symptoms to be effective [4]. There are two types of prevention.…”
Section: Introductionmentioning
confidence: 99%
“…The prevention of cardiovascular diseases must begin decades prior to the onset of symptoms to be effective [4]. There are two types of prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Here we confine our discussion to hypercholesterolemia. There is good reason to predict a very favorable risk/benefit ratio for early intervention, and there is a growing consensus that treatment-whether dietary or pharmacological-should start much sooner than is the practice today (17)(18)(19). There are understandable concerns about treating younger people and treating them for a lifetime.…”
mentioning
confidence: 99%
“…It was previously reported that increased TC levels detect elevated LDL-C levels with 44-50% sensitivity and 90% specificity (34). In order to diagnose dyslipidaemia more than one blood value is needed (35). In Slovenian children with elevated TC levels O5 mmol/l a fasting lipid profile (TC, LDL, HDL and triglycerides) was carried out consequently.…”
Section: Trends In Hypercholesterolaemia Prevalence From 2001 To 2009mentioning
confidence: 99%
“…The American Academy of Pediatrics recommends screening of children with a family history of premature CVD, a parental history of hypercholesterolaemia or when family history is unknown, and also screening of children with risk factors such as obesity, physical inactivity, hypertension, diabetes mellitus or smoking (35).…”
Section: Association Between Bmi and Tc Levelsmentioning
confidence: 99%